ChemInform Abstract: An Efficient Synthesis and in vitro Antibacterial Activity of Novel Spiro‐aminopyrimidones. Issue 18 (17th April 2014) - Balalaie, Saeed; Moghimi, Hamid; Bararjanian, Morteza; Rominger, Frank; Bijanzadeh, Hamid Reza; Sheikhahmadi, Masoumeh
Abstract: An easy and efficient method for the formation of the title compounds (IV) and (VIII) via three‐component reaction is developed.